Current knowledge and scientific trends in myokines and exercise research in the context of obesity - Letukienė, Austėja; Hendrixson, Vaiva; Ginevičienė, Valentina (Frontiers in Medicine, 2024)
The relationship between exercise and obesity has attracted increasing attention from researchers worldwide in recent years. The aim of the present study was to analyze the current knowledge and scientific trends of research into myokines and physical activity in the context of obesity and provide ideas for future research strategies to prevent obesity. The study conducted a comprehensive bibliometric analysis of 300 scientific publications related to myokines, physical activity, and obesity from 2004 to 2024. Applying the VOSviewer tool, the analysis revealed a significant increase over time in the number of publications on these topics, with a total of 1,142 related keywords identified. Key themes identified in the analysis included molecular processes, new organokines, skeletal muscle research, model organism studies, and human studies based on gender and age differences. The study highlighted the growing interest in the molecular mechanisms of obesity and role of myokines. Results showed a substantial increase in publications from 2014 to 2024, with a focus on new organokines (myokines, adipokines) and animal models. The analysis underscored the importance of myokines in modulating metabolic processes and their potential therapeutic implications in managing non-communicable diseases such as obesity and type 2 diabetes. Furthermore, the study revealed the close relationship between physical activity, myokine production, and the regulation of metabolism, stress response, and inflammation. Overall, the findings suggest the need for further research to better understand the molecular mechanisms underlying obesity and physical activity, as well as the potential therapeutic applications of myokines in preventing and treating obesity-related diseases.